A Knee Size-Independent Parameter for Malalignment of the Distal Patellofemoral Joint in Children - Ferdinand Wagner; Günther Maderbacher; Jan Matussek; Boris M. Holzapfel; Birgit Kammer; Jochen Hubertus; Sven Anders; Sebastian Winkler; Joachim Grifka; Armin Keshmiri (Advances in Orthopedics)
Introduction. Patellar instability (PI) is a common finding in children. Current parameters describing patellofemoral joint alignment do not account for knee size. Additionally, most parameters utilize joint-crossing tibiofemoral landmarks and are prone to errors. The aim of the present study was to develop a knee size-independent parameter that is suitable for pediatric or small knees and determines the malpositioning of the distal patellar tendon insertion solely utilizing tibial landmarks. Methods. Sixty-one pediatric knees were included in the study. The tibial tubercle posterior cruciate ligament distance (TTPCL) was measured via magnetic resonance imaging (MRI). The tibial head diameter (THD) was utilized as a parameter for knee size. An index was calculated for the TTPCL and THD (TTPCL/THD). One-hundred adult knees were analyzed to correlate the data with a normalized cohort. Results. The THD was significantly lower in healthy females than in males (69.3 mm ± 0.8 mm vs. 79.1 mm ± 0.7 mm; p<0.001) and therefore was chosen to serve as a knee size parameter. However, no gender differences were found for the TTPCL/THD index in the healthy adult study cohort. The TTPCL/THD was significantly higher in adult PI patients than in the control group (0.301 ± 0.007 vs. 0.270 ± 0.007; p=0.005). This finding was repeated in the PI group when the pediatric cohort was analyzed (0.316 ± 0.008 vs. 0.288 ± 0.010; p=0.033). Conclusion. The TTPCL/THD index represents a novel knee size-independent measure describing malpositioning of the distal patellar tendon insertion determined solely by tibial landmarks.